Economy or Chrematistics – Serbian Case - Andjelkovic, Petar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The nations are worth as much as it is worth their economies. In today's global world, people gain or lose independence primarily by how successful their economy is . Of course , freedom and independence of a people is defended in all fields , but the economic success is the key to success  to all the rest. A society that is for us and the former socialist countries , termed transition, represents a return to predatory capitalism and the way in hypocritical , orchestrated democracy ; it is now the world of lasting evil and bigger injustice that undermine the state and relentlessly pushing them into ,, peripheral capitalism " (Ljubisa Mitrovic). The word "economy" is of Greek origin and translated into our language it means " skill of housekeeping (economy)" . What we habitually continue to call economy in the world today and in Serbia , we can not call the skill of keeping. The term "economy" has long been superseded, in his place is the term " chrematistics " also a word of Greek origin that means inserted enrichment. This term in use is introduced by Aristotle. This ancient philosopher emphasized that the economy and chrematistics are antipodes and that chrematistics destructive to society. By its nature , it leads to the destruction of the economy. Practically , it can be called " destroyers skill of keeping the economy." Today in the world and Serbia do not have the economy , we have chrematistics (speculation on commodity markets , pyramid schemes , the development of the securities market , games on the stock market ... ) . Chrematistics the trick word , and that's why we can replace it with the term " casino - economy ." A new form of monarchy , which is expressed as a new imperialism , is not based on " cunning mind" (Hegel ) and the " spirit of the law " ( Montesquieu ) , but the " cunning of the economy " , which is dominated by raw (Hobbes ) laws of the market and where the economy becomes policies. Figure of societies of Eastern Europe , where the neoliberal social Darwinism , disenfranchising the largest population , has created an entire class of poor , who are now struggling to realize their right to work , confirms the emptiness of neoliberal democracy.  As a   result of chrematistics in transit societis " capitalism without capitalists " is created ( Mladen Lazic ) in which the capital , grabed during social conflicts, mediated by political  elites, by which the redistribution of accumulated social wealth ended up largely in private hands. If proved , and it is, that the current neo-liberal approach and form (paradigm ) does not give the expected , and so the required results , then the need to search for a new paradigm of development and more prominent . We need one another , a different view of society and especially its development , freed from the constraints and domination of the theory and methodology of the global powers imposed as the only desirable (required ) . So, we need a self-reflective approach to social issues especially in orthodox societies. It is a request that  it turned to itself and see their potential and opportunities. This paper is an attempt to draw attention to the devastating consequences of chrematistics in the world, and especially in our society , but also to make an effort to search for the " principle of hope " and point out the different possible directions of development of Serbian society. We are convinced that , as the basis of Western civilization with the neo-liberal development model is the social doctrine of Catholicism,  Orthodox civilization, which can and should be the centerpiece and developer " planetrly humanism " ( Danilo Z. Marković ) (which in the present Russia partly realized ) , there should be the social doctrine of Orthodoxy at the basis of Orthodox ethics and domestic economics.
Keywords: development; Serbian society; chrematistics; economy